DESCRIPTION OF ELDERLY DEPRESSION LEVELS - Livana PH; Yulia Susanti; Lestari Eko Darwanti; Rina Anggraeni (Fakultas Ilmu Keperawatan Universitas Islam Sultan Agung, Semarang, 2018)
Introduction: Increased life expectancy has an impact on the number of elderly people, thus changing health problems and social maps due to a decrease in the productivity of the elderly to organs. Methodology: Research with quantitative methods using descriptive study design. The sample size is 143 elderly. The technique of taking samples using purposive sampling, research has been conducted in the Village